Economical operation strategy of integrated energy system under fault state - Yuquan LIU; Xudong CHEN; Wen XIONG; Li WANG; Dongwen CHEN; Yong LI (Dianxin kexue)
A fault-state operation strategy for integrated energy systems based on multi-energy transfer was proposed.Firstly,an integrated energy system model was built to model each energy-supply device in the system using actual measurable parameters.Then,the calculation method of maximum energy supply capacity when energy-supply device fails was introduced,and the power constraint conditions of each equipment were obtained,and the power balance equations of cold/heat/electricity power were established.Then,set the lowest operating cost as the optimization goal,the objective function was solved by the linear programming method.Finally,taking a factory-level integrated energy system as an example,the rationality of the output changes of each equipment after using this strategy under several fault conditions was analyzed.It is pointed out that the strategy has three characteristics:the cost control effect is significant at low load situation,remarkably impacted by time-sharing energy prices,the outsourcing resource curve can predict the change of operating costs when fault occurs.